Interface memória e comunicação - da práxis ao ontológico : um (re)dimensionar da memória na comunicação a partir do contexto organizacional - Andreoni, Renata (2018)
(Re) Thinking about the memory and communication interface, based on the assumptions of the New Theory of Communication - NTC (MARCONDES FILHO, 2013a; 2013b; 2010a; 2010b; 2008; 2004) and the Philosophy of Henri Bergson (2006; 2005a; 2005b; 1999); 1988) is the journey we propose in this research. To accomplish this, in the light of complex thinking (MORIN, 2015a, 2015b, 2013, 2008), we set three objectives: To critically discuss the proposed interfaces between memory and communication, under the organizational memory configuration; to show possible dimensions that reveal how the organizational memory is configured, considering the academic propositions and their practices in the companies; (re) dimensioning the memory in the Communication, in addition to an instrumental approach. These objectives are designed to help us understand the landscapes that unveil at each step. The first landscape of this course is constituted by a critical and complex perspective of the praxis of academic productions and actions of different organizations on possible interfaces between memory and communication. For this, we consider the configuration of organizational memory, under which we show the predominance of the functional communication approach (SODRÉ, 2014a). In the second landscape we intertwine the NTC with the Bergsonian philosophical thought, constituting an ontological path for understanding memory in Communication. It is a theoretical study, in which we defend the thesis that the interface memory and communication can be established beyond a transmissive and instrumental relationship. Our efforts are aimed at developing an awareness to (re) think the communicational approach, having memory as a ubiquitous dimension in the relationships we establish in the continuous and indeterminate movement of life (I / Other).